FOREIGNIZATION AND DOMESTICATION IN VIETNAMESE-RUSSIAN TRANSLATION OF JOURNALISTIC TEXTS ON COUNTRY STUDIES (Journal of Foreign Language Studies, 2023)
This paper analyzed the use of foreignization and domestication in translating journalistic texts on country studies from Vietnamese to Russian. It aims to identify the dominant strategy used in translating non-equivalent words or word combinations in this specific type of texts by tallying, analyzing and comparing semes. The findings showed that the main strategy used for translating non-equivalent words or word combinations in the analyzed corpus is domestication. The results of this study can be used as a basis for larger-scale corpus-based research that investigates journalistic texts on country studies in order to identify features of the current foreign policies of Vietnamese press agencies.
Keywords: domestication; foreignization; translation; newspaper texts; area studies